Simulation algorithm of carrier transport subject to Lorentz force in semiconductor films - Kimura, Mutsumi; Hirako, Masaaki; Yamaoka, Toshifumi; Tani, Satoshi (Solid-state electronics, 2011)
Hall effect around a grain boundary in a polycrystalline semiconductor film. [Display omitted] ► We have developed a simulation algorithm of carrier transport subject to Lorentz force in semiconductor films. ► The Lorentz current is discretized with the drift and diffusion currents. ► The simulation algorithm is implemented in finite difference methods. ► Hall effect around a grain boundary in a polycrystalline semiconductor film is evaluated as a simulation example. ► It is found that a high Hall voltage is generated at the grain boundary. We have developed a simulation algorithm of carrier transport subject to Lorentz force in semiconductor films. The Lorentz current is discretized with the drift and diffusion currents, and the simulation algorithm is implemented in finite difference methods. Hall effect around a grain boundary in a polycrystalline semiconductor film is evaluated as a simulation example, and it is found that a high Hall voltage is generated at the grain boundary.